Production of a thin diamond target by laser for HESR at FAIR. (April 2016) - Balestra, F; Ferrero, S; Introzzi, R; Pirri, F; Scaltrito, L; Younis, H
Abstract: In the future hadron facility FAIR, the HESR ring will supply antiprotons in the momentum range 1.5-15 GeV/c as projectiles to study charm, strangeness and a wide range of other Physics topics. For all these reactions it will be necessary to use internal targets and in particular, for the production of systems with double strangeness, a solid 12 C target will be used. Inserting a solid target inside an antiproton ring creates two main problems: a large background on the detectors due to the overwhelming amount of annihilations and a strong depletion of the beam due to all the hadronic and Coulomb interactions of the antiprotons with the 12 C nuclei. The width of the target plays a crucial role in minimizing these unwanted effects. Two wire-shaped prototypes have been already realized, starting from a thin diamond disk. The wire shape has been obtained by using a femto-edge laser. One prototype has been submitted to irradiation by protons of 1.5 MeV and to simultaneous Back-Scattering control to test the impurity level, the 12 C density, the radiation hardness and possible phase modifications during irradiation. Both the prototypes have been submitted to Micro-Raman spectroscopy in order to scan the carbon phases along the width. The results show performances which satisfy the experimental requirements.